PENERAPAN PEMBELAJARAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SD NEGERI 011 BUKIT GAJAH KECAMATAN UKUI KABUPATEN PELALAWAN - Ipi Hanapiati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low results of students' mathematics learning. Of the 35students only 15 students (40.54%) who completed study results, while the average valueobtained by the students was 68.65. This study aims to increase the students' mathematicslearning through PMRI. This research is a class act who performed two cycles. Based on theresearch of learning outcomes and learning activities teachers and students expressedincreased. In the first cycle 1 meeting activities for teachers to get a score of 14 (70%), in thefirst cycle 2 meeting increased with a score of 15 (75%). In the second cycle 1 meeting obtaina score of 17 (85%) and the second cycle 2 meeting obtain a score of 18 (90%). Besides thestudent activity also increased in the first cycle of meeting one activity students obtain a scoreof 12 (60%), in the first cycle 2 meeting increased with a score of 16 (80%). In the secondcycle 1 meeting obtain a score of 17 (85%) and the second cycle 2 meeting obtain a score of17 (85%). The results of students' mathematics learning increases the basic score averagevalue obtained was 68.65 increase in the first cycle with an average value of 95.41 hasincreased in the second cycle with an average value of 97.97.